Encyclopedia of Analytical Surfaces - Krivoshapko, S.N; Ivanov, V.N (Springer International Publishing : Imprint: Springer, 2015)
This encyclopedia presents an all-embracing collection of analytical surface classes. It provides concise definitions  and description for more than 500 surfaces and categorizes them in 38 classes of analytical surfaces. All classes are cross references to the original literature in an excellent bibliography. The encyclopedia is of particular interest to structural and civil engineers and serves as valuable reference for mathematicians.